2021
DOI: 10.3390/jpm11020122
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of IL-15 and NKT in Tumor Microenvironment Predicts Poor Outcome of MYCN-Non-Amplified Neuroblastoma

Abstract: Immune tumor microenvironment (TME) in neuroblastoma (NBL) contributes to tumor behavior and treatment response. T cells and natural killer (NK) cells have been shown to play important roles in the neuroblastoma TME. However, few reports address the clinical relevance of natural killer T cells (NKTs) and interleukin-15 (IL-15), one of the crucial cytokines controlling the activation and expansion of NK/NKT cells, in NBL. In this study, we examined NKT immunoscores and IL-15 expression in both MYCN-amplified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…MYCN knockdown in high-expressing cell lines (SK-N-BE(2) and LAN-1) increased CCL2 mRNA transcript expression levels ( 50 ). Lower IL-15 and NKT cell immunoscores were found in MYCN -non-amplified samples in multiple databases of transcript expression in NBL, and IL-15 expression confirmed by RT-PCR in a separate sample of clinical cDNA NBL specimens ( 51 ). MYCN -amplified samples express high levels of the H3K9 histone-lysine methytransferases EHMT and EZH2, which directly contribute to low expression of CXCL9 and CXCL10 and a non-T cell-inflamed phenotype in primary tumor transcriptomic data as well as in human NBL cells, and can be reversed by targeted EHMT and EZH2 inhibitors ( 52 ).…”
Section: Immune Phenotypes Of Pediatric Solid Tumorsmentioning
confidence: 93%
“…MYCN knockdown in high-expressing cell lines (SK-N-BE(2) and LAN-1) increased CCL2 mRNA transcript expression levels ( 50 ). Lower IL-15 and NKT cell immunoscores were found in MYCN -non-amplified samples in multiple databases of transcript expression in NBL, and IL-15 expression confirmed by RT-PCR in a separate sample of clinical cDNA NBL specimens ( 51 ). MYCN -amplified samples express high levels of the H3K9 histone-lysine methytransferases EHMT and EZH2, which directly contribute to low expression of CXCL9 and CXCL10 and a non-T cell-inflamed phenotype in primary tumor transcriptomic data as well as in human NBL cells, and can be reversed by targeted EHMT and EZH2 inhibitors ( 52 ).…”
Section: Immune Phenotypes Of Pediatric Solid Tumorsmentioning
confidence: 93%
“…iNKT cells have also been coengineered with GD2-CAR + IL-15. IL-15 is (1) a key cytokine for iNKT cell development and homoeostasis [181] , [182] , (2) protective towards iNKT cell inhibition mediated by TAM [183], and (3) low IL-15 or iNKT cell presence within the neuroblastoma TME is associated with poor patient outcome [184] . CD28 GD2/IL15 CAR iNKT cells displayed enhanced persistence, antitumour activity, and tumour localisation in neuroblastoma mouse xenografts, as well as a reduced exhaustion profile in vitro [185] .…”
Section: Inkt Cellsmentioning
confidence: 99%
“…Moreover, two-thirds of human NB cell lines secrete CCL2, which mediates transendothelial migration of iNKTs in vitro, therefore, iNKT cells migrate toward NB cells in a CCL2-dependent manner, preferentially infiltrating MYCN nonamplified tumors that express CCL2 [49]. A study has recently shown that NKT cells can serve as a prognostic factor in MYCN-non-amplified NB [50]. Additionally, NB cells selectively express high levels of the ganglioside, GD2.…”
Section: Brain Cancers and Neuroblastomamentioning
confidence: 99%